Management of Facilities and Infrastructure to Improve the Quality of Education at SMP Negeri 2 Remboken - matindas, Anastasya fabiola; Lumapow, Harol R.; Mongdong, Romi J. (International Journal Labs, 2025)
The background of this research is to examine the extent of the role of infrastructure management to support the effectiveness of teaching and learning in the classroom. Basically, the management of good infrastructure facilities can support a conducive learning environment, which can encourage the quality of quality education. However, in many schools, including SMP Negeri 2 Remboken, the management of facilities and infrastructure still faces budget constraints, suboptimal maintenance, and lack of maximum utilization of facilities. The implementation of this research is aimed at (1) planning the management of facilities and infrastructure by the principal, (2) encouraging the creativity of the principal in its effective use, and (3) the ability of the principal to organize infrastructure facilities to support the quality of education at SMP Negeri 2 Remboken. The method implemented in the research is in the form of qualitative descriptive with data sources in the form of documentation, observation, and interviews with education staff, representatives and principals. The validity of the data is maintained by triangulation and member checks. In management, school principals show high creativity by utilizing local resources, optimizing BOS funds, establishing cooperation with the community, and implementing the use of simple technology to support the efficiency of the administration of infrastructure facilities. The principal's ability to organize facilities and infrastructure is reflected in the formation of an effective work team, clear division of tasks, and an orderly maintenance and inventory system.